2017
DOI: 10.1159/000468521
|View full text |Cite
|
Sign up to set email alerts
|

Role of HER2-Related Biomarkers (HER2, p95HER2, HER3, PTEN, and PIK3CA) in the Efficacy of Lapatinib plus Capecitabine in HER2-Positive Advanced Breast Cancer Refractory to Trastuzumab

Abstract: Objective: The aim of this study was to investigate the correlation between human epidermal growth factor receptor 2 (HER2)-related biomarkers and the treatment outcomes using lapatinib plus capecitabine (LC) and to evaluate the influence of the estrogen receptor (ER) status in trastuzumab-refractory HER2-positive advanced breast cancer. Method: Eighty patients were enrolled in this study. Total HER2, p95HER2, and total HER3 expression were quantified using the VeraTag assays. PTEN (phosphatase and tensin homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
(42 reference statements)
0
21
0
Order By: Relevance
“…Many studies did not find any demonstrable relationships between HER3 and patient survival [ 15 , 41 53 ]. Studies focusing on HER3 specifically in HER2 -amplified breast cancer [ 16 , 25 , 26 , 29 , 31 , 32 , 37 , 38 , 41 , 44 , 45 , 48 , 49 , 52 , 54 ] have not drawn conclusive results either. Interestingly, HER3 activation has been implicated as a molecular mechanism inducing inherent or acquired de novo resistance to anti-HER2 therapy [ 19 , 31 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies did not find any demonstrable relationships between HER3 and patient survival [ 15 , 41 53 ]. Studies focusing on HER3 specifically in HER2 -amplified breast cancer [ 16 , 25 , 26 , 29 , 31 , 32 , 37 , 38 , 41 , 44 , 45 , 48 , 49 , 52 , 54 ] have not drawn conclusive results either. Interestingly, HER3 activation has been implicated as a molecular mechanism inducing inherent or acquired de novo resistance to anti-HER2 therapy [ 19 , 31 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lapatinib is an orally available, small-molecule, reversible inhibitor of both EGFR and HER2 tyrosine kinases, and it has been approved for use in combination with capecitabine for the treatment of advanced HER2 -amplified breast cancer. 18 , 19 Additionally, it is reported that lapatinib has been used in the targeted chemotherapy for salivary ductal carcinoma with HER2 gene amplification. 20 It is necessary to elucidate the role of HER2 in tumor development and the mechanism by which lapatinib exerts effects on CXPA.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation of PFS with quantitative HER2, HER3 and p95HER2 expression has been examined in a similar cohort of trastuzumab-refractory patients treated with lapatinib and capecitabine [ 26 ]. No correlation with PFS was found for HER2 cutoffs, but a test for a potential U-shaped relationship with continuous HER2 was not performed.…”
Section: Discussionmentioning
confidence: 99%